2014
DOI: 10.1021/es502585s
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of N2O Formation during the Low-Temperature Selective Catalytic Reduction of NO with NH3 over Mn–Fe Spinel

Abstract: The mechanism of N2O formation during the low-temperature selective catalytic reduction reaction (SCR) over Mn-Fe spinel was studied. The in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) and transient reaction studies demonstrated that the Eley-Rideal mechanism (i.e., the reaction of adsorbed NH3 species with gaseous NO) and the Langmuir-Hinshelwood mechanism (i.e., the reaction of adsorbed NH3 species with adsorbed NOx species) both contributed to N2O formation. However, N2O select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
209
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(225 citation statements)
references
References 37 publications
15
209
1
Order By: Relevance
“…It has been reported that manganese-doped CeO 2 -WO 3 catalyst improves the de-NO x activity at lower temperature, whereas its poor selectivity toward N 2 restrains its employment. [27,28] Peng Antimony-doped CeO 2 -WO 3 /TiO 2 catalysts were prepared by a conventional ultrasonic-assisted impregnation method and employed for selective catalytic reduction of NO x with NH 3 at low temperature. Both experimental work and theoretical studies were employed to elucidate the effect of the antimony on promoting the CeO 2 -WO 3 /TiO 2 catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that manganese-doped CeO 2 -WO 3 catalyst improves the de-NO x activity at lower temperature, whereas its poor selectivity toward N 2 restrains its employment. [27,28] Peng Antimony-doped CeO 2 -WO 3 /TiO 2 catalysts were prepared by a conventional ultrasonic-assisted impregnation method and employed for selective catalytic reduction of NO x with NH 3 at low temperature. Both experimental work and theoretical studies were employed to elucidate the effect of the antimony on promoting the CeO 2 -WO 3 /TiO 2 catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that Lewis acid sites are benecial to NO conversion, which agreed with the result of activity measurements. 37 Besides, the Brønsted acid sites are advantage for the adsorption of NH 3 . 38 In fact, although gaseous NH 3 could be adsorbed on both Lewis acid sites and Brønsted acid sites during the SCR process, it was the Lewis acid sites that mainly exerted a positive effect.…”
mentioning
confidence: 99%
“…The Lewis acid site formed by Mo 6+ can enhance the acidity of the catalyst surface and strengthen the adsorption process of NH 3 on the catalyst surface. Previous studies [30,31] have shown that Mo could promote the dispersion of VO x species on the surface of TiO 2 . Importantly, V and W have a synergistic effect [32].…”
Section: Effect Of Tungstenmentioning
confidence: 97%
“…There are numerous possible reasons for this observation. Firstly, the depletion of the active ingredient (V2O5) could be the cause, the vanadium oxide could have been disseminated on the catalyst in an amorphous or highly dispersed form (Figure 8), or the molybdenum improved the dispersion of monolayer VOx species on TiO2 and the tungsten on the catalyst surface suppressed the progressive transformation of monomeric vanadyl species into crystalline V2O5 [31,47]. At the same time, the diffraction peak of WO3 appeared in the sample, but the diffraction peaks of WO3 did not appear, indicating that the dispersion of WO3 was slightly less, and WO3 did not sufficiently contact TiO2.…”
Section: Xrdmentioning
confidence: 99%